Gisekia pharnaceoides Restores Colonic Mucosal Homeostasis by Regulating Antioxidant Enzyme System and Cytokines Signaling in Ulcerative Colitis Mice Model - Javaid, Faraza; Aslam, Naveed; Arshad, Hafiza M.; Awan, Ambreen Mehmood; Majeed, Wafa; Jabeen, Qaiser (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Gisekia pharnaceoides Linn. (Aizoaceae), traditionally known as baluka saag or sareli is commonly found in the deep Cholistan region of Pakistan. It is used by the native community for the mitigation of a range of diseases, including inflammatory disorders and gastric ulcers. Objective: This study is designed to evaluate the defensive impact of G. pharnaceoides in acetic acid-induced ulcerative colitis in mice and to discover the mechanism for anti-inflammatory action. Methods: The ethanolic crude extract of G. pharnaceoides (Gp.Cr) was prepared and evaluated for phytochemical substances by preliminary screening and HPLC analysis. Anti-inflammatory activity of Gp.Cr (300 and 500 mg/kg) was examined by administration of 200 μl of 7.5% acetic acid intra- rectally to induce ulcerative colitis and colonic mucosal injury, while mucosal homeostasis was evaluated by disease activity index, colonic ulcer score, and hematological parameters. The anti-inflammatory potential was quantified by assessing antioxidant enzymes (SOD, CAT, GPX-1), lipid peroxides, nitric oxide, and cytokines (IL-1β, IL-6, TNF-α) immunoassays and further analyzed by histological analysis of colon tissues. Results: Phytochemical screening of Gp.Cr revealed the presence of alkaloids, phenols, flavonoids, steroids, tannins, and saponins, while HPLC analysis confirmed the presence of quercetin, gallic acid, coumaric and sinapic acid. In acetic acid-induced ulcerative colitis model, Gp.Cr (300 and 500 mg/kg) along with sulphasalazine (500 mg/kg) decreased disease activity index, ulcer scores, and hematological parameters. Gp.Cr showed a significant anti-inflammatory potential by increasing antioxidant enzymes and decreasing lipid peroxides, nitric oxide, and cytokines levels. Histopathological examination showed a significant decline in ulceration and tissue disruption. Conclusion: Hence, the findings confirmed the effectiveness of G. pharnaceoides crude extract in the treatment of ulcerative colitis and might be a promising remedy to manage inflammatory disorders.
Keywords: ulcerative colitis